Students' Perceptions About Family Harmony (Study of Adolescents from Low-Economy Families at SMKN 3 Padang) - Oktarizal, Rizki (Jurnal Riset Ilmu Pendidikan, 2022)
This research is motivated by the presence of students who feel they are treated differently from their parents and there are students who feel they have a bad way of communicating in the family. The purpose of this study was to describe students' perceptions of family harmony at low economic level at SMKN 3 Padang seen from: 1) Love between families 2) Mutual understanding among family members 3) Communication that exists within the family. 4) Cooperation between family members. This research was conducted using descriptive quantitative methods. The study population was 52 students who were selected by total sampling technique with 52 participants. The instrument used is a questionnaire. Meanwhile, for data analysis using percentage classification. Based on the results of research on students' perceptions of family harmony at low economic levels at SMKN 3 Padang, it can be seen from: 1) Affection between families is in the harmonious category. 2) Mutual understanding among family members is in the harmonious category. 3) Communication that exists within the family is in the harmonious category. 4) Cooperation between family members is in the harmonious category. Based on the results of the study, it is recommended for BK teachers to evaluate the programs that have been implemented and design service materials related to the harmony of the students' families